Amelia Falldorf: capstone - Falldorf, Amelia, artist and filmmaker (Colorado State University. Libraries, 2018)
The artist's statement: Technology itself may be, to some, nothing more than a tool with which to expedite the process of creation; one need only think of the Adobe Suite that dominates the graphics market. However, I view technology as more of a partner in creation; not exactly sentient, but certainly more complex and invested in the work than most people see on the surface. In the process of working alongside this technology, rather than simply with or through it, I find myself at an interesting place of discovery in which my work seemingly takes on a cognizance of its own, caught between the desired intentions of my own consciousness and the unconscious product of the code. Both myself and my work thrive within the confines of this partnership - while at the same time these confines help open unexplored doors to completely unseen forms of expression and entirely new ways to produce and conceptualize art. In my Electronic Arts practice, I am helping discover an entirely new visual world through the use of leading-edge computer techniques and the emerging possibilities of Virtual Reality. Pioneering a personal path in this still-budding medium is a passionate adventure that combines my more "traditional" interests and strengths as a Graphic Designer with a fierce drive to explore new methods of visual communication and technological husbandry.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Phenakistoiscope and Couplets - demo walkthrough videos have no spoken word. Alveo - installation footage has no audio.
Keywords: electronic art